Investigating issues confronting women participation in the building construction industry in Ondo state, Nigeria - Akinwale, Sanni Rotimi (Yayasan Mitra Persada Nusantara, 2024)
This study examined the issues confronting women participation in the building construction industry in Nigeria. The nature of work in the construction sector requires physical exactions and it is accompanied with stress which often leads to physical and muscular pain. Also the work environment at work site may not be so conducive as to consider the feminine nature of the woman. Four research questions guides the study and two research hypotheses was tested at 0.05 level of significance. The study adopts simple random sampling techniques in selecting the respondents so that each member of the population have chance of being represented in the sample. One hundred respondents were selected due to shortage of site available in Ondo State. The results revealed that building construction industry on women participation enable them build their confident in the work environment, increase their knowledge, encourage the development of career, reduces joblessness and encourage productivity. The study concluded that there is a discrimination and gender bias in the Ondo State building construction sector, and that some employers prefer to employ men for their construction projects, and the main reason behind was that, the state is predominantly a secular state and the majority of people has a unique culture, but in reality, male and female in terms of employment requirements and career development should have equal opportunity, the study recommends that the industry should improve the environmental factors in respect to women by introducing flexible work hours, reducing work load and making the work less tedious and stressful for women participation.